2017
DOI: 10.1002/nau.23245
|View full text |Cite
|
Sign up to set email alerts
|

Under what circumstances should stress incontinence surgery be performed at the same time as prolapse surgery? ICI‐RS 2015

Abstract: There is considerable uncertainty about the optimal method of managing women with vaginal prolapse and stress incontinence due to the different surgical techniques available. In particular the group of women with occult SUI are a challenge as the optimal diagnostic method has not yet been defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Some authors recommend that if the SUI and POP problem is treated vaginally, fascial repair or mesh reinforcement should be combined with a midurethral sling, because the SUI persistence rate is lower than when only the prolapse operation is performed [9,12]. If only prolapse surgery without continence surgery is performed in women with SUI and POP, the persistent urinary incontinence rate is 36 -71%, on average 63% [9]. In his study, Borstad et al found that 27% of women recover from SUI after just a prolapse operation [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some authors recommend that if the SUI and POP problem is treated vaginally, fascial repair or mesh reinforcement should be combined with a midurethral sling, because the SUI persistence rate is lower than when only the prolapse operation is performed [9,12]. If only prolapse surgery without continence surgery is performed in women with SUI and POP, the persistent urinary incontinence rate is 36 -71%, on average 63% [9]. In his study, Borstad et al found that 27% of women recover from SUI after just a prolapse operation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Lensen found that 38% of women with symptomatic SUI are cured after just a prolapse surgery [19]. If a woman has both a prolapse surgery and continence surgery, then the percentage of postoperative SUI is up to 40%, on average 11% [9]. However, the fact which cannot be ignored is that after the combination of prolapse and incontinence surgery, negative effects such as overactive bladder symptoms, obstructive voiding and complications, are more common, can call into question the outcome of this surgical procedure [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the World Health Organisation Quality of Life (WHOQOL), quality of life means an individual's perception of their position in life in the context of the culture and value systems in which they live. The quality of life is primarily influenced by physical health, interpersonal contacts and environmental characteristics [23,24]. Nowadays, doctors not only focus on extending the life of their patients, but also on improving its quality.…”
Section: Quality Of Life Of Patients With Pelvic Floor Static Disordersmentioning
confidence: 99%